The Use of Twitter by Politicians During June 2015 and November 2015 General Elections the Case of PDP - Polat, Ferihan; Özlem Özdeşim Subay (European Journal of Multidisciplinary Studies, 2016)
Nowadays, one of the mechanisms used by politicians in order to reach mass over is social media with the development of information and communication technologies. In this sense, as a free social media tool, Twitter, is one of the most used social media websites with the features of diffusion of thoughts directly on Internet and easy accessibility. This study evaluates that how and for what purposes Twitter is used by the candidates of Peoples' Democratic Party during the June 2015 and November 2015 General Elections in Turkey. For this aim, Twitter accounts of two co-chairman of PDP Selahattin Demirta? and Figen Yüksekda?; Deputy Chairman of Parliamentary Group of PDP Pervin Buldan; Parliament Vice President of Group of PDP ?dris Baluken and Administrative Authority of Parliament of PDP S?rr? Süreyya Önder are analyzed during two election times in one month period. As a result of this study, during two election times, differentiation of political language, decrease of peace rhetoric and hardening of opposite language as a parallel of the development of armed conflict in this period are observed in candidates of PDP which claims of being the party of Turkey peoples
Keywords: 2015 June General Elections, 2015 November General Elections, The Political Use Of Twitter, Peoples' Democratic Party.